Kansas meat marketing innovations - F.E. Jensen; D.B. Erickson; S.E. Trieb; H.J. Tuma (Kansas Agricultural Experiment Station Research Reports, 1972)
The U.S. system of producing, marketing, and distributing farm products has been heralded as the world's most efficient, with lower distribution costs than any other nation. Research continues to improve marketing through new methods and technology. Central cryogenic-frozen meat packaging is an example.
Keywords: Cattlemen& #x27; s Day; 1972; Report of progress (Kansas State University. Agricultural Experiment Station); 557; Beef; Marketing; Frozen meat; Tenderness